Parameter Genetik Karakter Agronomi pada Galur F1 Padi Hasil Persilangan Galur Murni dan Kultivar Lokal Indonesia: Parameter Genetik Karakter Agronomi pada Galur F1 Padi Hasil Persilangan Galur Murni dan Kultivar Lokal Indonesia - Eko Binnaryo Mei Adi; Sri Indrayani; Nana Burhana; Enung Sri Mulyaningsih (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Rice is one of the main sources of carbohydrates for Indonesian society. The development of new varieties depends on the availability of germplasm as the source genetic material. The development of new varieties can be done through artificial crosses (local cultivars and superior lines) for the creation of diversities. The research aimed to explore the genetics parameters from eight rice characters, for the selection program. The crossing was conducted by using four local cultivars and one pure line with diverse agronomic characters. Four hybrids (F1) were planted using completely randomized design with four replications, and five parental as the check varieties (landrace and pure line). The correlation coefficient was found that there was one character showed strong correlation almost all the character that is panicle weight. While high heritability was found in harvest age, panicle length, number of grain per panicle, 1000 grain weight, and plant high. Hybrids that showed negative heterosis for harvest age are from B14081H-296 x Salak and Dampak x Carogol, which have shorter harvest age compared to the average of the parental plant which is dominant gene action and additive.